PERSEPSI MASYARAKAT TERHADAP PERLUASAN AREAL KOLAM BUDIDAYA IKAN DI LAHAN RAWA LEBAK Studi Kasus Di Desa Tungkaran Kecamatan Martapura Kabupaten Banjar - Grace A. Mangalik; Ahmad Kurnain; Eka Radian; Pahmi Ansyari (Universitas Lambung Mangkurat, 2011)
This research aims to know the people perception on the increasing of the pond fish culture in lowland swamp, and to know the connection of the people perception with certain factors such as : the family income, extension, the length of business, the main business and the wide of the business areal.The data were compiled by survey using question-answer method which is based on the research variables, in which to get the quantitative data results. Research location was based on the purpossive sampling in Tungkaran villages which had the lowland swamp areal with had the fish culture in ponds, in Martapura areal, Kabupaten Banjar. Samples were taken by proportional from 30 persons with three strata research population where the family wich stay around the lowland swamp with 20 family, the local paddy-farmer family in lowland swamp with 50 family, and the pond-fish farmer family with 18 family; so that the total research population were 88 family. Analysis data for knowing the people perception on the increasing of the fish culture in lowland swamp, by counting the perception value (PV), while to know that there were conection or not by using Chi-Square Test (X2) (Setiawan, 2005), and to determine how closely the relationship between two variabels used in the test Koefisien Kontingensi (C) (Hadi, 1991).The result showed that : the people perception on the increasing of the fish-pond culture was 44,07%, in which this result indicated in decreasing criteria. The variable in which not connected with the people perception were the family income, the length of time business, the wide of business areal; while the variables which connected to the people perception were extension and the main business/job.